2011
DOI: 10.1002/cmdc.201000447
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Pharmacologic Effects of Gemcitabine and its Metabolite dFdU

Abstract: Recent evidence has shown that the gemcitabine metabolite, dFdU, is pharmacologically active. Though less potent, dFdU has a longer half-life and could potentiate or antagonize the activity of gemcitabine. Hence, studies were undertaken to evaluate the combined effects. Following chemical synthesis, an improved purification procedure for dFdU was developed (80 % yield; >99 % purity). Zebrafish phenotype-based embryo screens revealed no acute toxicity after gemcitabine or dFdU treatment. Only gemcitabine affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
(70 reference statements)
3
8
0
Order By: Relevance
“…Likewise,2 ' -deoxy-2',2'-difluorouridine (dFdU, Figure 1) is also as ubstrate for hTK. [15,16] Thec ombined interplay of steric constraints from both the 5-ethnyl group and the 2'-fluorine atoms is therefore responsible for the inability of hTK to phosphorylate dF-EdU.C onsistent with this conclusion, the superimposition model places the (2'R) fluorine atom of dF-EdU 2.20-2.32 f rom Va l174/Ile 175, and its terminal ethynyl carbon atom 2.67 f rom Thr163 (Figure 2b).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Likewise,2 ' -deoxy-2',2'-difluorouridine (dFdU, Figure 1) is also as ubstrate for hTK. [15,16] Thec ombined interplay of steric constraints from both the 5-ethnyl group and the 2'-fluorine atoms is therefore responsible for the inability of hTK to phosphorylate dF-EdU.C onsistent with this conclusion, the superimposition model places the (2'R) fluorine atom of dF-EdU 2.20-2.32 f rom Va l174/Ile 175, and its terminal ethynyl carbon atom 2.67 f rom Thr163 (Figure 2b).…”
mentioning
confidence: 78%
“…Both dFdC and dFdU are phosphorylated and incorporated into nucleic acids by endogenous human enzymes. [15] dFdU is significantly less toxic than dFdC [16] and was therefore selected for further development as ametabolic label. dFdU derivatives containing substituents at the 5-position, such as 2'-deoxy-2',2'-difluoro-5-bromouridine (BrdFdU), are nontoxic to mammalian cell cultures but they inhibit herpes virus replication.…”
mentioning
confidence: 99%
“…It remained statistically significant in the model, however, and further evaluation in larger studies are warranted to rule out the statistical significance of CDA (rs1048977; C>T) to be observed due to type-I error. We and others have demonstrated that dFdU contributes towards antitumour effect and toxicity, most probably through the formation of phosphorylated metabolites of intracellular dFdU (Pauwels et al , 2006; Veltkamp et al , 2008; Benyumov et al , 2011). As shown by others, we also found CL CR to be a significant predictor for the elimination clearance of dFdU, which is not surprising as dFdU is primarily excreted by the kidneys (Jiang et al , 2008).…”
Section: Discussionmentioning
confidence: 93%
“…The cytotoxic effect of gemcitabine is attributed mainly to the combined effects of the di- and tri-phosphate nucleosides, which leads to inhibition of DNA synthesis (Wong et al , 2009). Although much less potent than dFdCTP, dFdU is also formed intracellularly and can be phosphorylated to form triphosphate molecules with radiosensitising, cytotoxic and hepatotoxic effects (Pauwels et al , 2006; Veltkamp et al , 2008; Benyumov et al , 2011). …”
mentioning
confidence: 99%
“…Both dFdC and dFdU are phosphorylated and incorporated into nucleic acids by endogenous human enzymes 15. dFdU is significantly less toxic than dFdC16 and was therefore selected for further development as a metabolic label. dFdU derivatives containing substituents at the 5‐position, such as 2′‐deoxy‐2′,2′‐difluoro‐5‐bromouridine (BrdFdU), are nontoxic to mammalian cell cultures but they inhibit herpes virus replication 17.…”
Section: Methodsmentioning
confidence: 99%